2013
DOI: 10.1002/art.37932
|View full text |Cite
|
Sign up to set email alerts
|

A Matrix Metalloproteinase 1–Cleavable Composite Peptide Derived From Transforming Growth Factor β–Inducible Gene h3 Potently Inhibits Collagen‐Induced Arthritis

Abstract: Objective. Transforming growth factor ␤-inducible gene h3 (␤IG-H3), which is abundantly expressed in rheumatoid synovium, and matrix metalloproteinases (MMP) play important roles in the pathogenesis of rheumatoid arthritis (RA). The aim of this study was to determine the therapeutic efficacy of ␤IG-H3-derived peptides using MMP-1-dependent target tissue delivery in chronic inflammatory arthritis.Methods. Peptides developed from ␤IG-H3 derivatives, including the second and fourth YH peptides, the fourth fas-1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 43 publications
(73 reference statements)
0
32
0
Order By: Relevance
“…The T cell adhesion assay was performed as previously described with some minor modifications [22]. Briefly, recombinant human P-selectin-IgG-Fc chimera (0.1 μg/mL) or PAA-sLe X (0.1 μg/mL) was coated onto ELISA plates overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The T cell adhesion assay was performed as previously described with some minor modifications [22]. Briefly, recombinant human P-selectin-IgG-Fc chimera (0.1 μg/mL) or PAA-sLe X (0.1 μg/mL) was coated onto ELISA plates overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…26 Synovial tissue samples were obtained from patients with RA at the time of joint surgery. The age of arthritis patients ranged from 32 to 59 years.…”
Section: Materials Characterization Of Nanodrugmentioning
confidence: 99%
“…4,26,41 Therefore, identification of a comparable effect for DEX and a low dose of DEX-PEG-coated CNT on the expression of MMP-1 and MMP-3 is essential. Real-time PCR showed that both DEX and DEX-PEG-coated CNT diminished TNF-α-induced expression of MMP-1 and MMP-3.…”
Section: Gene Expression Of Pro-inflammatory Cytokines and Mmpsmentioning
confidence: 99%
“…Sixteen 10-week-old male DBA/1 mice were purchased from the Chinese Academy of Sciences (Shanghai, China) and were maintained under a controlled temperature (22˚C) and a 12-h light/dark cycle (light, 0700-1900 h), with access to a water and a standard diet ad libitum. Mice were immunized with Freund's adjuvant (Sigma-Aldrich, St. Louis, MO, USA)) and 100 µg bovine type II collagen (Chondrex, Redmond, WA, USA) at the base of the tail on day 0 and day 21 as previously described (7,8). Animal experimental protocols were approved by the Animal Committee of Zaozhuang Municipal Hospital (Zaozhuang, China).…”
Section: Methodsmentioning
confidence: 99%